Antibacterial effect of doxycycline-coated dental abutment surfaces. (11th September 2015) - Xing, Rui; Witsø, Ingun L; Jugowiec, Dawid; Tiainen, Hanna; Shabestari, Maziar; Lyngstadaas, Ståle P; Lönn-Stensrud, Jessica; Haugen, Håvard J
Abstract: Biofilm formation on dental abutment may lead to peri-implant mucositis and subsequent peri-implantitis. These cases are clinically treated with antibiotics such as doxycycline (Doxy). Here we used an electrochemical method of cathodic polarization to coat Doxy onto the outer surface of a dental abutment material. The Doxy-coated surface showed a burst release in phosphate-buffered saline during the first 24 h. However, a significant amount of Doxy remained on the surface for at least 2 weeks especially on a 5 mA–3 h sample with a higher Doxy amount, suggesting both an initial and a long-term bacteriostatic potential of the coated surface. Surface chemistry was analyzed by x-ray photoelectron spectroscopy and secondary ion mass spectrometry. Surface topography was evaluated by field emission scanning electron microscopy and blue-light profilometry. Longer polarization time from 1 h to 5 h and higher current density from 1 to 15 mA cm −2 resulted in a higher amount of Doxy on the surface. The surface was covered by a layer of Doxy less than 100 nm without significant changes in surface topography. The antibacterial property of the Doxy-coated surface was analyzed by biofilm and planktonic growth assays using Staphylococcus epidermidis . Doxy-coated samples reduced both biofilm accumulation and planktonic growth in broth culture, and also inhibited bacterial growth on agar plates. The antibacterial effect was stronger for samples of 5 mA–3 h coated with a higher amount of Doxy compared to that of 1 mA–1 h. Accordingly, an abutment surface coated with Doxy has potential for preventing bacterial colonization when exposed to the oral cavity. Doxy-coating could be a viable way to control peri-implant mucositis and prevent its progression into peri-implantitis.